A Mediator subunit, MDT-15, integrates regulation of fatty acid metabolism by NHR-49-dependent and -independent pathways in C. elegans - Taubert, Stefan (Cold Spring Harbor Laboratory Press, 2006)
The Caenorhabditis elegans Nuclear Hormone Receptor NHR-49 coordinates expression of fatty acid (FA) metabolic genes during periods of feeding and in response to fasting. Here we report the identification of MDT-15, a subunit of the C. elegans Mediator complex, as an NHR-49-interacting protein and transcriptional coactivator. Knockdown of mdt-15 by RNA interference (RNAi) prevented fasting-induced mRNA accumulation of NHR-49 targets in vivo, and fasting-independent expression of other NHR-49 target genes, including two FA-Δ9-desaturases (fat-5, fat-7). Interestingly, mdt-15 RNAi affected additional FA-metabolism genes (including the third FA-Δ9-desaturase, fat-6) that are regulated independently of NHR-49, suggesting that distinct unidentified regulatory factors also recruit MDT-15 to selectively modulate metabolic gene expression. The deregulation of FA-Δ9-desaturases by knockdown of mdt-15 correlated with dramatically decreased levels of unsaturated FAs and multiple deleterious phenotypes (short life span, sterility, uncoordinated locomotion, and morphological defects). Importantly, dietary addition of specific polyunsaturated FAs partially suppressed these pleiotropic phenotypes. Thus, failure to properly govern FA-Δ9-desaturation contributed to decreased nematode viability. Our findings imply that a single subunit of the Mediator complex, MDT-15, integrates the activities of several distinct regulatory factors to coordinate metabolic and hormonal regulation of FA metabolism.